The role of yeasts during the ripening of salami - Osei-Abunyewa, Akua Abrafi (University of the Free State, 1999)
Yeasts play a substantial role in the processing of salami, being present at high numbers during the ripening stages contributing to aroma and flavour development. Accordingly, the yeasts occurring as natural microflora in commercial salami were quantified, isolated and identified according to conventional identification and enumeration techniques. Depending on conditions, the yeasts grew to maximum populations of 107duIg during the ripening stages. Characterization of the naturally contaminating yeasts of commercial salami revealed 108 yeast species, belonging to 12 genera. The yeasts most frequently isolated were from the genera Debaryomyces, Rhodotorula, Bul/era, Candida, Cryptococcus, Trichosporon and Schwanniomyces in that order. Low appearances of Pichia, Galactomyces, Sporobolomyces, Sterigmatomyces and Torulaspora were observed. Debaryomyces hansenii, Rhodotorula mucilaginosa, Bul/era variabilis and Cryptococcus albidus were established as representing the typical yeast community associated with salami. These species were frequently isolated from the meat, during processing and maturation. The most frequently isolated yeast species, was D. hansenii, isolated on every sampling occasion. The isolated yeasts were examined based on relevant key properties that governed their growth and survival in fermented meat, and proposed as representative selective characteristics to determine a good starter culture. All the yeasts were tolerant to 4-8% NaCl and 80-240ppm nitrite. All the yeasts proved to be non-proteolyic with the exception of Trichosporon beigeli~ whereas lipolitic activity appeared variable. Two predominating yeast isolates, Debaryomyces hansenii and Debaryomyces polymorphus, exhibited relevant qualities regarding fermentation of meat. Consequently, they were applied in the formulation as starter cultures in an attempt to prepare a salami based on yeast fermentation. The incorporation of D. hansenii, individually, or in association with conventional starter cultures, resulted in a product with improved taste and reduced maturation time.
Dissertation (M.Sc. (Microbiology and Biochemistry))--University of the Free State, 1999
Keywords: Yeast; Fermentation; Processed foods